Faktor-Faktor Yang Berpengaruh Terhadap Penerimaan Aplikasi Brilian Dengan Model Utaut - Banjuradja, Andre Mentaya; Sunarto, M.J Dewiyani; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
According to a decree number 290/KPT-03B/VII/2014 about implementation of Hybrid Learning Model clause six, lecturer Stikom required to implement Brillian as a learning medium. This is not the first time Stikom Surabaya implementing an e-learning application. From many kinds of e-learning that has been applied previously, none of application that can be accepted as a medium of teaching and learning, whereas already a lot of material and non-material sacrificed to implement a variety of e-learning. Try to overcome these problems by conducting a comprehensive evaluation and adequate empirical studies in accordance with theories. One theory could be used to evaluate the acceptance of information technology is the Unified Theory of Acceptance and Use of Technology (UTAUT) which was developed by Venkatesh in 2003. The result of this study case found the opposite result with Venkatesh theory. The four factors (Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Condition) does not influence significantly to increase Behavioral Intention or Use Behavior. Only Behavioral Intention proven to have significant influence on the Use Behavior. Besides moderating variables (age, gender, experience and volunteerism) was not found to have a significant influence in intent and actual use of Brilliant.